Análisis de discurso de la Ley Orgánica de Bienestar Animal. - Duque Arteaga, Ivanova Karolina (2016)
This article aims to analyze the journalistic discourse of El Comercio and El Telégrafo on the events around the Animal Welfare Organic Law, published during the period October 2014-May 2015, a period of more news about flow is law. For this the method of discourse analysis proposed by Teun Van Dijk is used. The article is the result of a much broader analysis that the assessment of the impact of this law on the mass media referred Ecuadorians. The analysis shows that there was a positive treatment to the Organic Law of Welfare in both newspapers analyzed. This treatment is done from the use of imagery that enhance the awareness of the reader to animals and their owners. Among them those related to the animal is part of the family, it is heroic, cheerful and brings joy among others. A strategy of quite marked polarization in which opponents of the law are perpetrators and victims animals and owners are also used. The law is designed as a matter of progress, development and prosperity for society as a whole not just for those with animals today. The analysis leads to conclusion.